Theatrum Sabaudiae. Das Kupferstichwerk der Herzöge von Savoyen: Entstehung, Rezeption, Funktionswandel (1660-1740) - Tammaro, Silvia (2021)
The Theatrum Sabaudiae (1682) is an illustrated publication that vividly depicted the territories of the Duchy of Savoy through detailed copper engravings and panegyric descriptions. The book was an important instrument of courtly representation, with text and images providing a sumptuous as well as persuasive means of self-presentation for the Duke of Savoy, his policies and his possessions. After the first edition, the book was printed in six further editions that were aimed not only at an audience of aristocrats but also at book collectors and scholars.